2017
DOI: 10.1186/s12943-017-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomal proteins in cancer diagnosis

Abstract: Exosomes are emerging as a new type of cancer biomarkers. Exosome is a bilayered nano-sized vesicle secreted by various living cells in all body fluids. Based on the expanding albeit incomplete knowledge of their biogenesis, secretion by cells and cancer cell-specific molecular and genetic contents, exosomes are viewed as promising, clinically-relevant surrogates of cancer progression and response to therapy. Preliminary proteomic, genetic and functional profiling of cancer cell-derived or cancer plasma-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
244
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(246 citation statements)
references
References 140 publications
0
244
0
2
Order By: Relevance
“…Recently, exosomes have drawn significant attention as essential mediators of intercellular communication under both physiological and pathological conditions . Recent studies suggested that serum, saliva, or urine exosomal cargos can be used as potential biomarkers for low‐invasive diagnoses of cancers . Diagnosis of chronic liver disease at an early stage instead of irreversible and life‐threatening advanced stages is challenging because of the lack of noninvasive or low‐invasive approaches and long asymptomatic disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exosomes have drawn significant attention as essential mediators of intercellular communication under both physiological and pathological conditions . Recent studies suggested that serum, saliva, or urine exosomal cargos can be used as potential biomarkers for low‐invasive diagnoses of cancers . Diagnosis of chronic liver disease at an early stage instead of irreversible and life‐threatening advanced stages is challenging because of the lack of noninvasive or low‐invasive approaches and long asymptomatic disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing evidences that cancer‐derived exosomes may contribute to tumorigenesis and metastasis and served as a potential biomarker . Meanwhile, due to their presence in most body fluids, exosomes might sever as noninvasive clinical biomarkers . Accordingly, we extracted exosomes from CL187 cell supernatant and CRC patient peripheral blood, and demonstrated that LEA/PODXL highly accumulated in the exosomes using ND‐1‐probed western blotting assay.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Meanwhile, due to their presence in most body fluids, exosomes might sever as noninvasive clinical biomarkers. 60 Accordingly, we extracted exosomes from CL187 cell supernatant and CRC patient peripheral blood, and demonstrated that LEA/PODXL highly accumulated in the exosomes using ND-1-probed western blotting assay. To our best knowledge, it is the first time to find the LEA/PODXL expression in cancer cell-derived exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prevalent strategies is to integrate immunoaffinity isolation of exosomes into the microfluidic device. The capture antibodies, such as exosome‐associated tetraspanins (e.g., CD9, CD63, and CD81), or cancer‐associated proteins (e.g., EpCAM and GPC‐1), can be immobilized onto the surfaces of microchannels or microstructures. For example, PDMS micropillar arrays functionalized with multiwall carbon nanotubes (MWCNTs) have been used for rapid exosome isolation with >80% recovery under an optimized sample flow rate of 1 mL h −1 ( Figure a) .…”
Section: Isolation and Detection Of Exosomes In Microfluidicsmentioning
confidence: 99%